IMPLEMENTASI METODE FORWARD CHAINING TERHADAP SISTEM PAKAR GANGGUAN KEHAMILAN - Sri Lestari; Ayuk Ambar Kusuma (CKI ON SPOT, 2021)
Pregnancy is a very valuable thing for a mother, who certainly brings happiness to every family. But sometimes not all pregnancies go smoothly as expected. Sometimes there are pregnancy disorders that carry a high risk. To avoid these disorders, a pregnant woman should consult with a pregnancy expert. However, not all mothers can easily access consultations with doctors or midwives, many obstacles are faced such as limited time or high costs. This lack of information can bring disaster to pregnant women. Then made an application that can be easily accessed anywhere and anytime at a low cost, which can provide information to pregnant women about disorders in pregnancy. This application is like an expert who can answer complaints experienced during pregnancy. By using the forward chaining method, which is a forward flow by describing the symptoms experienced so that a diagnosis of the disease that might be suffered can be obtained, so that further action can be taken to reduce the risk even higher.